Binding of Epstein-Barr virus small RNA EBER-1 to the double-stranded RNA-activated protein kinase DAI. - Clarke, P A (1991)
Epstein-Barr virus encodes two small RNAs, EBER-1 and -2, that are abundantly expressed in latently infected cells. Recent evidence suggests a role for EBER-1 in regulation of translation since this RNA is able to prevent the inhibition of protein synthesis by double-stranded RNA in rabbit reticulocyte lysates. We show here that EBER-1 that has been synthesized in vitro forms a complex with the dsRNA-activated inhibitor of protein synthesis DAI, a protein kinase that specifically phosphorylates polypeptide chain initiation factor eIF-2. Gel retardation assays and UV crosslinking experiments indicate that complex formation is specific for EBER-1 and requires the presence of some secondary structure in the molecule. RNA competition studies show that EBER-1-DAI complex formation is not inhibited in the presence of other small RNA species, heparin or the synthetic double-stranded RNA, poly(I).poly(C). SDS gel analysis reveals the existence of two forms of the crosslinked complex, of 64-68kDa and 46-53kDa, both of which are recognized by anti-DAI antibodies in immunoprecipitation experiments. These data suggest that EBER-1 regulates protein synthesis through its ability to interact with DAI.